Male or Female, who is better? Student's Perception of the E-Module in Physics-Mathematics Vector Material - Astalini Astalini; Darmaji Darmaji; Dwi Agus Kurniawan; Auliya Ramadhanti (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2022)
This study aims to see how students from different classes perceive the e-Module Mathematics Physics I on vector material, besides that variations in gender differences will also be tested in this perception. The type of research used is descriptive quantitative research. The population in this study were students of Physics Education class 2019 with a sample of 80 students in regular classes A and C. The data were analyzed descriptively and inferentially by using the IBM SPSS Statistic 22 application which consisted of descriptive test, normality test, homogeneity test, and t-test analysis. The results obtained are normal data with a sig of 0.190, and homogeneous with a sig of 0.305. While the t-test obtained a sig value of 0.019 for gender differences in class A, and 0.017 for gender differences in class C. So Ho is rejected and Ha is accepted, meaning that there are significant (significant) differences in perceptions based on gender in each class A and C. Where the perception of male students is higher than the perception of female students, but overall students give a good perception of the Mathematics Physics e-module I on Vector material.